FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PENGELOLAAN LIMBAH TAHU DI SEMPADAN SUNGAI KEMUNING KOTA BANJARBARU - Islamiaty, Ayuni; Fatmawati, Fatmawati; Yunita, Rizmi; Rahman, Mijani (EnviroScienteae, 2024)
The Banjarbaru City area has three tofu producers who are currently operating in Banjarbaru Selatan District, Banjarbaru City. The three tofu producers do not yet have a Wastewater Treatment Plant (IPAL) so that the liquid waste produced is disposed of directly into the Kemuning river which is not far from the location. The research objective was to analyze the production process and tofu waste generated in the tofu management process and to analyze the factors that influence the behavior of tofu processed waste management in the Kemuning River Border, Banjarbaru City. The research method used is a quantitative descriptive method. The results of the study show that the results of data processing, knowledge (X1) of Mba Ana's tofu craftsmen has a greater influence of knowledge, namely as much as 88.7%, Baihaqi tofu craftsmen as much as 88.3%, Dinanti tofu craftsmen as much as 88.6%. The effect of the attitude (X2) of the Dinanti tofu craftsmen is as much as 91%, Mba Ana's tofu craftsmen is 79%, Baihaqi tofu craftsmen is 83.7%. The effect of action (X3) is that the Baihaqi tofu craftsmen are larger by 78.8%, Mba Ana's tofu craftsmen are 72.9%, Mba Ana's tofu craftsmen are 71.2%. The effect of education (X4) on Mba Ana's tofu craftsmen was greater by 79.8%, Baihaqi tofu craftsmen 79.8%, Dinanti tofu craftsmen 73%. The factors that affect waste management for the three tofu producers are categorized as sufficient because the value is more than 50%, in the implementation of tofu processing, Dinanti tofu craftsmen dispose of liquid waste in a simple shelter, while Mba Ana and Baihaqi tofu craftsmen still throw waste into the river.